Informatics for equitable recovery : supporting equitable disaster recovery through mapping and integration of social vulnerability into post-disaster impact assessments - Lallemant, David (2020)
Disasters continue to present tremendous obstacles to sustained development progress and the wellbeing of communities around the world. Key to mitigating the long-term impacts of disasters is the ability to rapidly respond and recover in ways that build resilience and protect hard-fought development gains. However, the information systems needed to support such resilient and equitable recovery are currently lacking, such that decision makers often end up gathering evidence for recovery decisions in ad-hoc ways rather than systematically. This study focuses on the information and the data that influence early decision-making processes after a disaster. We call this project Informatics for Equitable Recovery because we have built frameworks for developing information systems that focus on identifying not only those who are impacted but also those who are least able to recover so that we can inform more equitable long-term recovery processes. Based on data from the 2015 Gorkha earthquake in Nepal, we developed tools to map post-disaster building damage more accurately, making use of all the data that gets produced after a disaster. We implemented a household survey, interviews, and more to understand and usefully account for the complexities of disaster impact beyond building damage. We also developed a metric to estimate differential post-disaster need and extreme vulnerability in order to inform early decision making that fosters more effective and equitable recovery processes. We close this report with recommendations for use of the tools and ideas we share throughout.